1995
DOI: 10.1097/00000539-199503000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Effects of Premedication for Children

Abstract: Cardiovascular and respiratory effects of pediatric preanesthetic premedication have received only minimal attention, probably because most children tolerate such drugs without apparent ill effect. In children with congenital heart disease or other serious illness, there is often reluctance to use premedication. We sought to determine whether different premedication regimens produced significant cardiorespiratory effect. A randomized prospective study of the cardiovascular and respiratory effects of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

1996
1996
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
1
8
0
3
Order By: Relevance
“…Our study supports the data presented by Audenaert and colleagues 13 who found that the combination of intranasally administered racemic ketamine 5 mg·kg -1 and midazolam 0.2 mg·kg -1 did not produce significant cardiovascular and respiratory side effects. Taking into account that racemic ketamine has approximately half the potency of s-ketamine, 14 this dosage is comparable to our group K2.…”
Section: Side Effectssupporting
confidence: 93%
See 1 more Smart Citation
“…Our study supports the data presented by Audenaert and colleagues 13 who found that the combination of intranasally administered racemic ketamine 5 mg·kg -1 and midazolam 0.2 mg·kg -1 did not produce significant cardiovascular and respiratory side effects. Taking into account that racemic ketamine has approximately half the potency of s-ketamine, 14 this dosage is comparable to our group K2.…”
Section: Side Effectssupporting
confidence: 93%
“…Thus, we can only state that, based on this limited study, no serious complications were encountered. This and previously published studies on nasal ketamine and midazolam in children [8][9][10]13,18 without any reports of serious complications are no formal safety proof. One theoretical serious complication would be the penetration of s-ketamine and midazolam through the cribriform plate, giving rise to high central nervous system levels.…”
Section: Side Effectsmentioning
confidence: 74%
“…Sie wird übereinstimmend als sicheres und effektives Verfahren angesehen, die kardiovaskulären Wirkungen als unbedeutend beschrieben: Herzminutenvolumen und Blutdruck bleiben gleich bei steigender Herzfrequenz und fallendem Schlagvolumen [3]. Wegen der v. a. bei Säuglingen nicht selten auftretenden Atemdepressionen sollte Methohexital nur von Ärzten verabreicht werden, die Erfahrung in der Sicherung des Atemwegs haben [27].…”
Section: Weiteres Schicksal Von Avertinunclassified
“…Audenaert et al [3] beobachteten keine Depression von Hämodynamik oder Atemantrieb (Ketamin 5 mg/kg plus Midazolam 0,2 mg/kg, nasal gegeben).…”
Section: Ketamin Als Zusatz Zu Midazolamunclassified
“…und Applikationsformen (nasal, rektal, i.m., s.c.) sind in der Literatur zu finden, ohne dass sich aufgrund der Datenlage die Bevorzugung eines Regimes eindeutig rechtfertigen ließe. [10].…”
Section: Pharmakologische Prämedikationunclassified